Role of Ca2+ and Ethanol in The Process of Flocculation - S. DAKE, MANJU; P. JADHAV, JYOTI; B. PATIL, NARAYAN (Asian Journal of Chemistry, 2010)
In addition to the two pools of glycogen, cytoplasmic and cell wall bound insoluble glycogen, the third pool of glycogen at the cell surface was confirmed by amyloglucosidase treatment in yeast cell. Amyloglucosidase removes the cell surface a-glucans so that the yeast cells lose their capacity to form aggregates in the presence of concanavalin-A. Cells grown in a medium containing Ca2+ ions exhibit higher amount of cell surface a-glucans. Addition of both Ca2+ and ethanol to yeast culture medium results in increased both insoluble glycogen content and surface α-glucans which play an important role in the flocculation process. Hence both Ca2+ and ethanol enhance flocculation in yeast cells. The flocculance level correlates with the level of cell surface α-glucans and the rate of flocculation of yeast. Highly flocculant yeast cells have higher level of cell surface a-glucans and rapid setting behaviour.